Patients’ Contentment with Wasfaty and Health Services in Community Pharmacies in Tabuk and the Factors Associated with It - Prabahar K; Alharbi LK; Alsharif ST; Alaqais ZM; Almarwani MJ; Alatawi HA; Sankar K (Patient Preference and Adherence)
Kousalya Prabahar,1 Lama Khalid Alharbi,2 Sara Talal Alsharif,3 Zood Mobarak Alaqais,4 Maha Jarallah Almarwani,5 Hanaa A Alatawi,5 Karthik Sankar6 1Department of Pharmacy Practice, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 2United Doctors Hospital, Jeddah, Saudi Arabia; 3Alnahas Pharmacy, Tabuk, Saudi Arabia; 4DaVita Clinic, Tabuk, Saudi Arabia; 5Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 6Sri Ramachandra Faculty of Pharmacy, Sri Ramachandra Institute of Higher Education and Research (DU), Porur, Tamilnadu, IndiaCorrespondence: Kousalya Prabahar, Department of Pharmacy Practice, Faculty of Pharmacy, University of Tabuk, Tabuk, 71491, Saudi Arabia, Email kgopal@ut.edu.saBackground: Patient contentment is an indicator of the quality of pharmacy services. Pharmacists can recognize and resolve drug-related issues, provide patients with the information they need, raise patient contentment, and improve the standard of patient care. Utilizing E-prescription (Wasfaty) is one of the key services in the healthcare system that achieves the aspiration of the Kingdom’s Vision 2030 by improving efficiency, accuracy, and convenience for patients and healthcare professionals. The present study seeks to evaluate the effect of the Wasfaty app on patients’ contentment in the Tabuk region and the factors associated with it.Methods: A cross-sectional study was conducted from January to March 2024 in Tabuk among patients using the Wasfaty app. Data was collected using a convenience sampling technique and a self-administered questionnaire. The analysis of the data was conducted using SPSS software version 27.0. Descriptive statistics (mean, percentage, standard deviation, p-value) illustrate the respondents and their characteristics. Mantel-Haenszel test was used to estimate the odds ratio. Significance was reached when p < 0.05.Results: A total of 422 beneficiaries participated in the study. The majority of respondents were female (55.2%) and the majority were under 50 years. Only 23.5% of the included population visit the community pharmacy for chronic diseases. A majority of the participants (68.7%) viewed Wasfaty services positively. Availability of the Wasfaty service, medication availability, detailed instructions by pharmacists, efficiency of the Wasfaty app, and service speed and waiting time were positively associated with their overall positive experience.Conclusion: The results of our study demonstrated overall high contentment with Wasfaty app and its effectiveness in improving patient medication management. The factors associated with the patient’s contentment helps in promoting the quality of care provided to the patients.Keywords: Wasfaty app, community pharmacy services, contentment